Disuse induced by the spine rectification vest: experimental study - Rinaldo Roberto de Jesus Guirro; Eder João Arruda; Carlos Alberto da Silva (Universidade de São Paulo, 2014)
The spine is the main support and movement axis of the locomotor system, and numberless clinical conditions may require that this structure be submitted to functional restriction. Among the non-invasive treatments used in spinal or appendicular skeleton injuries, the immobilization of the spine is used as a rehabilitation strategy. Because of the functional restrictions generated by restraining devices used on the spine, the proposal of this study was to adapt a spinal orthosis on rats, thus mimicking the immobilization of corrective vests and assessing the energetic conditions of thoracic muscles after 12 weeks of application. Wistar rats that were 42 days old were used in this study (post-weaning period), followed-up for 12 weeks in 2 groups called control (C) and rectification vests (R), which were made of PVC to immobilize the spine. The following concentrations were evaluated: glycogen (GLY) of the paravertebral muscle and the thorax; total proteins and DNA (TP/DNA) and interleukin-6 (IL-6). The normality Kolmogorov-Smirnov test was used for statistical analysis, followed by the Tukey test. A 5% level was established for all of the calculations. It was observed that group R presented 12% less body mass and GLY stores 21% lower; the ratio between TP/DNA was in average 6.6% lower; IL-6 concentrations were in average 25% higher. The study shows that the movement restriction in the spine leads to energetic crisis and compromised muscular development. More studies should be conducted with this model to generate physical therapy strategies that could reduce muscle compromise after spine immobilization.